THE INFLUENCE OF LOCAL GOVERNMENT EXPENDITURE ON ECONOMIC GROWTH IN THE DISCIPITIES/CITIES OF WEST SUMATRA PROVINCE 2019-2023 - Laura Maulina; Rini Elvira; Yuwarman Mansur; Sofia Ridha (RADJA PUBLIKA, 2025)
This study aims to determine and analyze the extent to which local government spending affects economic growth in the regencies/cities of West Sumatra Province. This study supports the theory of John Maynard Keynes. According to Keynes, local government spending plays an important role in determining the rate of economic growth. If local government spending decreases, economic growth will also decline. The research method used in this study is quantitative associative. The type of data used in this study is secondary data with data collection techniques obtained from the Central Statistics Agency (BPS) of West Sumatra Province. The data used is for 5 years, from 2019 to 2023. The tool used in data processing is the SPSS 26 program. The data analysis technique used in this study is simple linear regression analysis. The results of the study were conducted using the t-test and R Square with alpha 0.05 and a confidence level of 95%. The results of this study indicate that Local Government Spending has a significant influence on Economic Growth by 85.1% and the remaining 14.9% is influenced by other variables not examined in this study, such as poverty, concentration of economic activity, unequal income distribution, consumption, investment, exports, and imports. Therefore, it is necessary to implement effective and efficient local government policies to achieve the desired economic growth goals. To achieve high economic growth, the role of the government is required, namely by managing government spending by allocating budgets to ensure that government spending is in accordance with plans and goals that have been set.